Design and evaluation of a coalition-led obesity initiative to promote healthy eating and physical activity in low-income, ethnically diverse communities: the Go! Austin/Vamos! Austin initiative - Alexandra van den Berg; Aida Nielsen; Nika Akhavan; Carmen Llanes Pulido; Semonti Basu; Aliya Hussaini; Christine Jovanovic; Kathryn Janda; Laurence Denis; Nalini Ranjit (BMC, 2019)
Abstract Background Go! Austin/Vamos! Austin (GAVA) is a coalition-led health initiative that targets low-income communities with disparities in access to healthy food and physical activity. The purpose of this initiative was to increase healthy eating and physical activity among residents by facilitating access to food and physical activity opportunities through environmental and policy changes. Although GAVA is ongoing, this paper describes the original GAVA intervention and the 5-year evaluation study (2013-2018), presenting selected baseline data obtained through its cohort sub-study. Methods To assess the impact of GAVA, the evaluation plan included multiple sub-studies and involved collection of quantitative, qualitative, and observational data at different levels. The main cohort sub-study followed 313 parent-child dyads over 5 years. Annually, parents completed self-administered surveys regarding awareness and use of community assets/resources as well as their diet and activities. Heights and weights also were measured. Results Cohort participants were primarily Hispanic (87%), very low-income (77%), and food insecure (58%), with high overweight/obesity prevalence among both parents (81%) and children (41%). Awareness and use of community physical activity and healthy eating resources were low, and reported barriers to using these resources were many. Engagement in physical activity and healthy eating also was low. Conclusions Given the baseline statistics, GAVA resident teams chose and implemented strategies to address the noted barriers and low usage of community resources. This approach built community capacity and governance. Both the GAVA intervention approach and evaluation protocol can serve as models for other community initiatives to be implemented in other locations and contexts.